Structure and dynamics of the upper montane rain forests of Sri Lanka - Werner, Wolfgang L.; Balasubramaniam, Sinnathamby (Tropical forests in transition, 1992)
The upper montane rain forests of Sri Lanka occur above 1500 m in the Central Highlands and Knuckles mountains of Sri Lanka. There is a marked difference in floristic composition and physiognomy against the lower montane rain forests of middle elevation. The most frequent plant families are Lauraceae (Cinnamomum, Litsea, Actinodaphne) and Myrtaceae (Syzygium, Eugenia, Rhodomyrtus), followed by Clusiaceae (Calophyllum, Garcinia), Theaceae (Gordonia, Ternstroemia), Elaeocarpaceae and Symplocaceae. Gymnosperms and Fagaceae, which are prominent in the mountains of Asia and other regions of the world, are lacking in South India and Sri Lanka. This makes the mountain flora of Sri Lanka very peculiar, as the montane species derive from the rain forest flora of the lowland (cf. Werner 1984, 1985). The analysis of trace elements in leaves of forest trees in Sri Lanka shows, that those of lowland rain forest and upper montane rain forest are very similar in contrast to deciduous forest and mangrove. The content of aluminium in trees of the upper montane rain forest is ten times higher than in other forest types. Canopy-dieback has been observed on the western slopes, where heavy winds increase the effect of dry spells. Frost damage sometimes occurs along the edge of the forest and in open gaps (cf. Werner 1988). The dynamics of the UMRF still have to be studied in permanent plots. Regeneration seems to be poor, as the trees grow slowly and the seedlings are suppressed by the dense undergrowth of Strobilanthes. Knowledge about natural regeneration of these forests is essential for proper conservation management, as they have been heavily disturbed above many tea estates and settlements.